2022
DOI: 10.3390/foods11162447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Application of a Green Preservative Strategy on Minced Meat Products: Antimicrobial Efficacy of Olive Mill Wastewater Polyphenolic Extract in Improving Beef Burger Shelf-Life

Abstract: The mincing process of raw meat favors microbial spoilage as well as chemical and enzymatic oxidation processes. In order to limit this degradative process, preservatives are routinely added to minced meat products. The role of olive mill wastewater polyphenolic extract as a replacement for synthetic preservatives in beef burger was assessed. The antioxidant capacity of the extract experimentally added to beef burger was evaluated using the oxygen radical absorbance capacity method (ORACFL) to assess the shelf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…According to other studies, tyrosol suppresses the activity of cyclooxygenase enzymes, and hydroxytyrosol can cause protein denaturation [ 44 ]. All these mechanisms could be responsible for the increase in the bacterial lag phase and the reduction in the exponential growth phase (log phase) detected in different bacterial populations [ 10 , 23 ]. It is possible that when a high number of bacteria were present in the meat, all the mechanisms that interfere with bacterial adaptation to the environment could not be overcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other studies, tyrosol suppresses the activity of cyclooxygenase enzymes, and hydroxytyrosol can cause protein denaturation [ 44 ]. All these mechanisms could be responsible for the increase in the bacterial lag phase and the reduction in the exponential growth phase (log phase) detected in different bacterial populations [ 10 , 23 ]. It is possible that when a high number of bacteria were present in the meat, all the mechanisms that interfere with bacterial adaptation to the environment could not be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the last decade, numerous studies have described the effects of polyphenols obtained from plant extracts on foodborne pathogens and spoilage bacteria [ 5 , 6 , 7 , 8 ], both in vitro and in meat models. A few studies have also reported on the antimicrobial effects of specific polyphenols, preventing bacterial growth when directly applied to fresh meat or added to minced meat preparations [ 9 , 10 ]. Furthermore, the synergistic or antagonistic interactions of phenolic compounds with multiple other chemicals may influence the antibacterial properties of plant extracts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[37] The aroma of a volatile oil is defined by the chemical makeup of the oil, which changes according to the plant species, harvest time, climate, and region from which the oil is pressed. [38][39] The volatile oil can be smelled when it is heated. [40] There are a broad array of compounds that make up essential oils, and many of these substances have been isolated.…”
Section: Role Of Essential Oil In Fragrancementioning
confidence: 99%
“…In recent times, the increased awareness of the impact of the diet on human health has encouraged the scientific community and food industries to search for effective alternatives to the chemical antimicrobial additives commonly used in food preservation [ 5 ]. The use of these compounds indeed, although strictly regulated [ 6 ], is considered with mistrust by consumers, due to their potential long-term adverse effects on health [ 7 , 8 ]. Some of the main synthetic antimicrobials, approved by regulatory agencies, are: sodium benzoates and propionates, potassium sorbates, sorbic acid, sulphites, chlorides, nitrites, triclosan, nisin, natamycin, potassium lactate, ascorbic acid, citric acid, tartaric acid, etc.…”
Section: Introductionmentioning
confidence: 99%